Surrogate (replacement) motherhood, or should the uterus be rented? - Donev, Dejan (Fakultet za odgojne i obrazovne znanosti, Sveučilište Josipa Jurja Strossmayera u Osijeku, Hrvatska, 2019)
After the birth of the “test-tube baby,” the triumphant success of reproductive technologies has dramatically accelerated scientific research in many fields and given hope to couples struggling with the problem of infertility. However, at the same time, new and numerous moral, ethical, bioethical, legal, social, cultural, and gender dilemmas and controversies have been imposed, especially in countries where trends of negative population growth are increasingly emphasized. These assisted reproductive technologies are making a difference, and not just from the aspect of medicine towards sterility. They are also profoundly affecting social and cultural patterns of marriage, partnership, parenting, and gender. Surrogate or surrogate motherhood, as part of the field of reproductive technology issues, calls for an urgent rethinking of the possibilities for institutionalized motherhood practices in contemporary society and its effects in everyday life. In other words, it is an attempt to demystify, denaturalize, and re-evaluate maternal norms, which always indicate relationships in specific material conditions of centralizing or decentralizing public or private power or sociability. However, they primarily and above all are related to the possibility of prior (bio)ethical evaluation, which would
Surogat (zamjensko) majčinstvo, ili treba li se maternica iznajmljivati?
Keywords: surrogate motherhood; bioethical evaluation; reproductive technologies; human dignity; fertility tourism